Kemandirian pada Anak yang diasuh orangtua tunggal - Ningsih, Sulistia; , Dr. Taufik, M.Si., Ph.D.D (2015)
The purpose of this study was to describe independence in children who cared for single parents. Informants in this study managed by purposive sampling. The informant is a child who lived with his mother 7 -12 years age range. This research was conducted by 4 respondents. This study used a qualitative approach by collecting data using interview techniques that are equipped with observation. The results obtained from the study were children aged 7-12 years. The study found that the behavior of the child self can do yourself is wash and dress themselves, sweeping the house and occasionally raking leaves, washing the dishes, went to school with bike, play themselves in the environment, and save money on their own without any coercion of parents. Single parent is a single parent, only one parent to meet the needs of their families because one parent has died, divorced, or no clear hungan of both, but this study focuses on the study of single parent mother.